Bacterial diversity in high Andean grassland soils disturbed with Lepidium meyenii crops evaluated by metagenomics - Huaraca-Meza,F. (2022)
Abstract Soil quality is usually determined by its physical-chemical characteristics without taking into account the bacterial communities that play a fundamental role in the chemical decomposition of plant nutrients. In this context, the objective of the study was to evaluate bacterial diversity in high Andean grassland soils disturbed with Lepidium meyenii cultivation under different gradients of use (first, second and third use) and crop development (pre-sowing, hypocotyl development and post-harvest). The sampling was carried out in the Bombón plateau in the central Andes of Peru, during the rainy and low water seasons, by the systematic method based on a specific pattern assigned in a geometric rectangular shape at a depth of 0 - 20 cm. The characterization of the bacterial communities was carried out through the metagenomic sequencing of the 16S rRNA. 376 families of bacteria were reported, of which it was determined that there was a significant change in bacterial composition and distribution in relation to use pressure. There were no major changes due to the development of Lepidium meyenii. The families most sensitive to use pressure and soil poverty indicators were Verrucomicrobiaceae, Acidobacteraceae and Aakkermansiaceae.